Optimization of Receptive and Expressive Arabic Language Skills Through Deep Learning-Based Learning Methods - Diva Sekar Nur Haqim; Rayhan Muhamad Ridwan; Abdul Malik Qimanullah; Ruly Saepul Azhar; Nanang Kosim (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
In its development, the implementation of learning has now reached the concept of deep learning. Deep learning can be defined as an approach that emphasizes creating a learning environment and learning process that is conscious, meaningful, and enjoyable, through the mind, heart, and senses, body, in a holistic and integrated manner. Deep learning is expected to enhance the learning process, particularly in the development of language skills, both receptive and expressive. This study aims to investigate the integration of deep learning in the development of receptive and expressive language skills. This study employs a qualitative approach with a literature review, as the data obtained are descriptive and expressed in words. The results of this study indicate that various learning methods, such as Project-Based Learning, Inquiry-Based Learning, Collaborative Learning, and Problem-Based Learning, are highly relevant because they not only support the achievement of academic competencies but also encourage emotional and social engagement among learners. Each method offers stages or syntax that can be adapted to the language skills that must be developed. Thus, integrating deep learning principles and appropriate methods will result in a learning process that is effective and transformative. Dalam perkembangannya, pelaksanaan pembelajaran kini telah mencapai konsep pembelajaran mendalam (deep learning). Deep learning dapat didefinisikan sebagai suatu pendekatan yang menekankan pada penciptaan lingkungan dan proses belajar yang sadar, bermakna, serta menyenangkan, melalui keterlibatan pikiran, hati, pancaindra, dan tubuh secara holistik serta terintegrasi. Deep learning diharapkan mampu meningkatkan kualitas proses pembelajaran, khususnya dalam pengembangan keterampilan berbahasa, baik reseptif maupun ekspresif. Penelitian ini bertujuan untuk mengkaji integrasi deep learning dalam pengembangan keterampilan berbahasa reseptif dan ekspresif. Penelitian ini menggunakan pendekatan kualitatif dengan metode kajian pustaka, karena data yang diperoleh bersifat deskriptif dan disajikan dalam bentuk kata-kata. Hasil penelitian menunjukkan bahwa berbagai metode pembelajaran seperti Project-Based Learning, Inquiry-Based Learning, Collaborative Learning, dan Problem-Based Learning sangat relevan diterapkan, karena tidak hanya mendukung pencapaian kompetensi akademik, tetapi juga mendorong keterlibatan emosional dan sosial peserta didik. Setiap metode memiliki tahapan atau sintaks yang dapat disesuaikan dengan keterampilan berbahasa yang ingin dikembangkan. Dengan demikian, integrasi prinsip-prinsip deep learning dan metode yang tepat akan menghasilkan proses pembelajaran yang efektif dan transformatif.